A Legal Review of Criminal Offenses Related to Animal Quarantine for Animals Lacking Health Certificates Under Law No. 21 Of 2019 - Umar Suryanaga; Noenik Soekorini; Fitri Ayuningtyas (Eduvest - Journal of Universal Studies, 2026)
Animal quarantine is an essential measure to prevent the entry, exit, and spread of quarantinable animal diseases that may endanger public health, food security, and the sustainability of biological resources. In practice, cases still occur involving the transportation and distribution of animals without health certificates, which may constitute legal violations and pose threats to both animal and human health. This study aimed to analyze the legal regulation concerning criminal acts related to animal quarantine involving animals without health certificates under Law Number 21 of 2019 concerning Animal, Fish, and Plant Quarantine, as well as to examine the implementation and law enforcement against offenders based on applicable criminal provisions. The research method used was normative legal research with statutory and conceptual approaches. The legal materials consisted of primary, secondary, and tertiary sources, which were analyzed qualitatively.The legal framework governing animal quarantine is regulated under Law Number 21 of 2019 concerning Animal, Fish, and Plant Quarantine, Law Number 18 of 2009 concerning Animal Husbandry and Animal Health as amended by Law Number 41 of 2014, along with relevant implementing regulations. The results of the study indicate that every importation and transportation of animals must be accompanied by a health certificate issued by an authorized official as proof of animal health and as a measure to prevent disease transmission. Violations of this obligation may result in administrative and criminal sanctions in accordance with the provisions of Law Number 21 of 2019.